Inspiring Excellence: How Transformational Leadership Shapes Supervision in Islamic Religious Education - Ali, Umar; Kotten, Natsir B; Abbasov, Ramil (JURNAL AL-TANZIM, 2025)
This study examines the implementation of transformational leadership in the supervision of Islamic Religious Education (PAI) at Madrasah. While transformational leadership has been widely discussed in general educational settings, its application specifically in PAI supervision remains underexplored. The research employs a descriptive qualitative case study, using observations, interviews, and document analysis to gather data. The study finds that supervisors at Madrasah serve as role models and inspirational figures, motivating teachers and students to strive for higher educational standards. Supervisors also foster teacher innovation and creativity by encouraging new teaching methods tailored to student needs, providing mentorship, and offering training opportunities. Support teacher professionalism by helping educators overcome challenges and facilitating continuous professional development. The findings contribute to the understanding of how transformational leadership practices can be applied within the unique context of Islamic Religious Education. This study emphasizes the need for leadership that not only manages but also inspires and empowers educators to create a positive learning environment.